TOTAL FACTOR PRODUCTIVITY CHANGE IN THE REIT INDUSTRY: THE CASE OF MALAYSIAN REITS DURING AND POST GLOBAL FINANCIAL CRISIS - Chuweni, Nor Nazihah; Isik, Ihsan; Blake, Andrea (PLANNING MALAYSIA, 2019)
The paper examined productivity changes for the Malaysian Real Estate Investment Trust (M-REITs) using a non-parametric approach of Malmquist Productivity Index (MPI) of Data Envelopment Analysis (MPI-DEA). Data was attained from M-REIT annual reports, Thomson Reuters Datastream and Osiris via Bureau Van Dijk for 2007-2015. The non-parametric approach of MPI-DEA examined the Total Factor Productivity Change (TFPCH), Technological Change (TECHCH), Efficiency Change (EFFCH), Pure Technical Efficiency Change (PEFFCH) and Scale Efficiency Change (SECH) indices. On average, the M-REIT industry has faced 14.91% of productivity regress during 2007-2015 period, comprising 49.90% of efficiency increase and 33.40% technological regress. The decomposition of the productivity change index suggests that Malaysian REIT productivity changes were mainly due to efficiency change rather than technological change. These findings could help M-REIT managers to formulate ways to enhance their REIT productivity. The findings are also applicable to similar Shariah compliant real estate investment or socially responsible investment.